2020
DOI: 10.1002/oby.22703
|View full text |Cite
|
Sign up to set email alerts
|

BMI and Medically Certified Long‐Term Sickness Absence Among Japanese Employees

Abstract: Objective In contrast to the association between excess weight and sickness absence (SA), the association in relation to underweight has been under‐researched. This study aimed to examine the effects of BMI at both extremes of its distribution on SA. Methods Data came from the Japan Epidemiology Collaboration on Occupational Health study of 77,760 workers aged 20 to 59 years (66,166 males, 11,594 females). Information was collected on medically certified long‐term SA (LTSA) (i.e., SA lasting ≥ 30 consecutive d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
(57 reference statements)
1
7
0
Order By: Relevance
“…Depressive disorders were the most frequent causes of sickness absence among the various mental disorders, accounting for approximately half of all psychological illnesses 23 ) . Endo et al 29 ) reported that LTSA among Japanese employees often involved episodes of LTSA, with mental and behavioral disorders being more frequent than the three major physical disease categories (NP, MS, and CC) contributing to LTSA. Our results are consistent with these previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Depressive disorders were the most frequent causes of sickness absence among the various mental disorders, accounting for approximately half of all psychological illnesses 23 ) . Endo et al 29 ) reported that LTSA among Japanese employees often involved episodes of LTSA, with mental and behavioral disorders being more frequent than the three major physical disease categories (NP, MS, and CC) contributing to LTSA. Our results are consistent with these previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…J-ECOH is an ongoing epidemiological study investigating the health determinants of Japanese workers. 23 25 For the present study, we used the data of three participating companies that provided information on overtime working hours. Of the 64,633 full-time workers who received a health check-up in Fiscal Year 2011 (or 2010, if information was not available in 2011) in these companies, we excluded: those who did not provide information on overtime work ( n = 7,922), those who were aged <20 years old or ≥60 years old in 2011 ( n = 4,632); those who were on LTSA in April 2012 ( n = 125); those with a history of cancer ( n = 461), cardiovascular disease (CVD) ( n = 490) or mental illness ( n = 1,164) as having any of these conditions may be associated with employment restrictions; and those with missing information on any of the covariates ( n = 105).…”
Section: Methodsmentioning
confidence: 99%
“…This study used data from the Japan Epidemiology Collaboration on Occupational Health Study (J-ECOH). J-ECOH is an on-going epidemiological study investigating the health determinants of Japanese workers [23][24][25] . For the present study, we used the data of three participating companies that provided information on overtime working hours.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…The present prospective cohort analysis was based on data of the Japan Epidemiology Collaboration on Occupational Health (J-ECOH) Study, which is an ongoing epidemiological survey investigating health determinants in workers in Japan across various industrial sectors, e.g., steel, chemical, gas, plastic product manufacturing, health care. [19][20][21] We invited companies in Kanto and Tokai area in Japan for the study through an occupational physician network (convenience sampling). All the employees for whom the occupational physicians are in charge of health management were eligible for the study.…”
Section: Study Settingmentioning
confidence: 99%